Implementasi Logika Fuzzy Mamdani dalam Sistem Pendukung Keputusan Untuk Penanganan Kesehatan Gizi Balita di RS Citra Arafiq Sawangan - Sunandar, Dede (Dinasti Research, 2025)
This research aims to develop a web-based decision support system (DSS) using the Fuzzy Mamdani method for handling the nutritional status of toddlers at Citra Arafiq Sawangan Hospital. The main problem faced by this hospital is that the management of nutritional data for toddlers is still manual, so the process of assessing nutritional status takes a long time and is less effective. The Fuzzy Mamdani method was chosen because of its ability to handle data uncertainty and provide precise results through fuzzification and defuzzification processes. This system groups toddlers based on variables such as age, weight and body length to produce nutritional status such as malnourished, undernourished, normal, tall or obese. The implementation of this SPK has shown a significant increase in efficiency and is quite helpful for medical personnel in accessing data and analyzing the condition of toddlers in real-time, so that health care can be carried out more quickly and precisely. With this website-based system, Citra Arafiq Hospital has succeeded in speeding up the decision-making process and providing recommendations for appropriate treatment related to toddlers' health and improving service quality. The evaluation results prove that this system makes data management easier and effectively supports decision making.